New bioanalytical microemulsion Electrokinetic chromatography method for the simultaneous determination of Trifluridine with its metabolites and Tipiracil in rat plasma: Application to pharmacokinetic studies - Mohamed Hefnawy; Adeeba Alzamil; Hatem Abuelizz; Mona AlShehri (Elsevier, 2019)
A Microemulsion Electrokinetic Chromatography method coupled with diode array detector (MEEKC-DAD) was developed for the first time and found to be efficient, sensitive, and selective for the simultaneous analysis of Trifluridine (FTD), and its metabolites 5-(trifluoromethyl) uracil (FTY) and 5-carboxy-2'-deoxyuridine (5CDU), and Tipiracil (TIP) in rat plasma. Sample pre-treatment involved a simple protein precipitation from plasma using acetonitrile. The separation was achieved using a fused silica capillary (65 cm total length, 55 cm effective length and 50 µm i.d.) and a microemulsion solution consisted of 1.66% sodium dodecyl sulfate (SDS), 0.91% heptane, 6.61% 1-butanol, and 90.72% borate buffer (20 mM, pH 9.5). Electrophoretic separation was carried out at 20 °C and 20 kV. The samples were injected for 40 s at 20 mbar and detected simultaneously at 205 nm. The electrophoretic parameters indicated that the developed MEEKC-DAD method permitted complete resolution of the analytes within 13 min. The developed method was fully validated according to the FDA guidelines for bioanalytical method validation. The method was linear in the range 200-4000 ng/ml for FTD, FTY, 5CDU, and 100-1000 ng/ml for TIP. The intra/inter-day accuracy and precisions were ≤4% for all drugs. Extraction recovery and stability were also assessed and were within acceptable range. After being validated, the method was applied for the determination of the studied drugs in plasma samples collected from rats injected intraperitoneally with a combination of FTD and TIP. The results obtained were used to study the pharmacokinetics of FTD with its metabolite and TIP in rat plasma. Keywords: Microemulsion electrokinetic chromatography (MEEKC), Colorectal cancer, Trifluridine/Tipiracil, Metabolites, Bioanalysis, Pharmacokinetics